COVID-19 Control in Community Hospitals: Experience From Four Community Hospitals in Beijing, China. (3rd March 2022) - Wang, Hongyu; Yuan, Ping; Tang, Chong; Guan, Zhenpeng; Xiang, Pingchao; Chen, Xin; Zhang, Dan; Li, Qi; Hu, Shoukui; Bo, Tianhui; Gu, Jin
By September 20, 2021, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been pandemic in 237 countries and regions, resulting in 228, 506, 698 confirmed cases and 4, 692, 361 deaths. At the same time, a total of 1123 cases of COVID-19 had been confirmed in Beijing, China. Peking University Shougang Hospital has 4 community hospitals with 174 staff members, covering 230, 000 residents in Shijingshan district, Beijing. The community hospitals were the basic units of China's healthcare system for public health services, as the main battlefield for screening and controlling of COVID-19. We reported our experience about the prevention of SARS-CoV-2. We suggest that community hospitals should change their process for admitting patients. While the screening of suspected cases of COVID-19 is vital, patients with suspected infections should be isolated immediately.